Activities of the militia in Ukraine to ensure road safety in the 1950s - V. A. Grechenko; S. I. Subota (Bulletin of Kharkiv National University of Internal Affairs)
In the 1950s, the daily functions of the militia continued to include combating violations of street traffic rules and controlling the decrease in motor vehicle accidents. The accident rate on the roads of the republic at that time remained high. An analysis of the current state of road safety shows that the level of accidents, injuries and deaths on the roads was influenced by such objective factors as the level of development of the regulatory framework, the technical condition of vehicles, the level of development of the road network, its quality, and weather and climatic conditions. Subjective factors included the level of legal culture of road users (drivers and pedestrians), the degree of their readiness to participate in traffic, the professional qualifications and material and technical equipment of the employees of the State Automobile Inspection. During this period, state bodies carried out significant, but ambiguous in quality, rule-making work, the purpose of which was to develop measures aimed at improving both objective and subjective conditions that affected the state of road safety and were of a mutually agreed nature. The established driver training mechanism was one of the important components of the effective operation of the road safety system. Therefore, the activities of state bodies, in particular the State Automobile Inspection of the Ministry of Internal Affairs of the Ukrainian SSR, were aimed at forming not only stable skills in driving vehicles among the drivers, but also behavioral stereotypes that require compliance with legal norms in the field of road safety. At the same time, it was necessary to develop and legally establish criteria for assessing the quality of their training in the relevant institutions. Militia bodies carried out quite active work to improve the situation with road accidents, which included measures of administrative influence, involvement of the public in monitoring violations of traffic rules, various propaganda activities, but its effectiveness was ultimately insignificant.